RESIDENTIAL CARE IN ISRAEL: PRINCIPLES FOR CONSTRUCTING A COMPUTERIZED SYSTEM FOR GATHERING DATA, PLANNING INTERVENTIONS, AND EVALUATING OUTCOMES - Shapira, Hadas; Reznikovski-Kuras, Anna; Arazi, Tal (International Journal of Child, Youth and Family Studies, 2025)
The project described here aimed to assist the Residential Placement Unit of the Ministry of Welfare and Social Affairs in developing tools for planning interventions for children in their care, monitoring activities and practices, and assessing outcomes. A major requirement was to ensure that the data produced would be relevant to field workers and support their daily therapeutic work with the children. The tools also facilitate ongoing follow-up on the children’s characteristics, needs, strengths, and prior interventions, including evaluating their effectiveness. This information is organized and can be presented in outputs tailored to the needs of field workers, supervisors, and policymakers. Key principles that guided the project were: collaboration among a multitiered team; involvement of service recipients and care leavers (“experts by experience”); balancing the needs of policymakers, staff and field workers; use of standardized and accepted terminology; reliance on a shared measurement framework; and use of outcome-based thinking to structure the system and its components. The implementation of such a computerized system often raises apprehension or resistance among both managers and staff. To address this, a lengthy and in-depth process of building trust took place, including training sessions that communicated the rationale behind the system’s development and the principles underlying its design, and the establishment of a structured feedback mechanism to assess the staff’s acceptance of the system. The system was successfully assimilated and is in routine use in all the residential care facilities of the Ministry of Welfare. Several factors were identified to explain this success: the commitment of the administration of the Residential Placement Unit to this project; the availability of an existing computerized system upon which to develop the project; and the involvement of the research team in the characterization of the system, training the staff, and refining and modifying the system based on the feedback received.